Colorless polyimides derived from rigid trifluoromethyl-substituted triphenylenediamines. (24th April 2023) - Bao, Feng; Lei, Huanyu; Zou, Bingyu; Peng, Weifeng; Qiu, Luhao; Ye, Fan; Song, Yaohao; Qi, Fuling; Qiu, Xuepeng; Huang, Mingjun
Abstract: Colorless polyimides (CPIs) have wide applications in flexible photoelectric devices, thanks to their high transparency and heat-resistance. Herein, three rigid aromatic triphenylenediamine monomers containing varied number and position of trifluoromethyl (-CF3 ) substituents, i.e., c -3FTP, c -6FTP, and s -6FTP, were designed. The corresponding CPI films were fabricated by polycondensation with the commercial 4, 4'-(hexafluoroisopropylidene)diphthalic anhydride (6FDA) or 1, 2, 4, 5-cyclohexanetetracarboxylic dianhydride (CHDA). Due to the steric hindrance of –CF3 groups, three diamines all exhibit large torsion angles within 46.1°–87.1° between benzene rings determined via single crystal analysis. The structure-property analysis reveals that –CF3 substitution located on the central phenyl ring facilitates the high glass transition temperature ( T g ), while more –CF3 substitutions are beneficial for high optical transparency. Among all the CPIs, the 6FDA/ c -6FTP film exhibits the most remarkable balance in thermal, optical, and dielectric properties, including high thermal resistance ( T g  = 385 °C, T d5%  = 537 °C), excellent optical transparency (λcutoff  = 350 nm, T 450  = 84.5%, and b * = 1.44), low dielectric nature ( D k  = 2.84, D f  = 0.0053) at 10 GHz, and high surface hydrophobicity ( θ  = 100°, W H2O  = 0.25%). This systematic study would complement the basic structure-property relationship of aromatic CPIs and inspire rational development of high-performance aromatic CPI materials toward applications in flexible display or 5G technology. Graphical abstract: Image 1 Highlights: Three rigid fluorinated triphenylenediamines with large steric torsion of 46.1°-87.1° were designed and synthesized. The 6FDA/ c -6FTP film exhibits well-balanced thermal ( T g = 385 °C), optical ( T 450 = 84.5%, and b ∗ = 1.44), and dielectric properties. The structure-performance relationship of CPI films was investigated via both experiments and DFT calculations.